Is The Corporate Governance Important for Firm Value? - Afera Wijayanti; Etty Murwaningsari; Anthony Ferdinand (Journal of Applied Business and Technology, 2025)
This objective of this study is to examine the influence of Corporate Governance and Earning Management on the Firm Value with the moderating is Sales Growth. With cross-sectional data from 2023 from 227 cyclical and non-cyclical companies listed on the Indonesia Stock Exchange, and this study employs a quantitative methodology with the goal of analyzing. Data analysis uses Moderated Regression Analysis or MRA with Eviews 13.0 software to test the moderating effect of Sales Growth. With cross-sectional data from 2023 from 227 cyclical and non-cyclical companies listed on the Indonesia Stock Exchange, this study employs the quantitative methodology with the goal of analyzing The study's findings show that Earning Management (? = 0.414, p < 0.01) and Corporate Governance (? = 0.241, p < 0.01) significantly increase Firm Value. Sales Growth functions as a pure moderator, according to moderation analysis, while the link between Corporate Governance and Firm Value is more strongly moderated by the CG×SG interaction (? = 0.320, p < 0.05), and the association between Earning Management and Firm Value is moderated by the EM×SG interaction (? = -0.485, p < 0.01). Sales growth is a pure moderator that enhances the beneficial impact of corporate governance while diminishing the impact of the earnings management on firm value, according to this result.